The Iron Lady : Margaret Thatcher, from grocer's daughter to prime minister - Campbell, John, 1947- (New York : Penguin Books, 2011)
The Iron Lady, the definitive Margaret Thatcher biography, is available just in time for the movie starring Meryl Streep as one of the most infamous figures in postwar politics. Whether you love her or hate her, Margaret Thatcher's impact on twentieth-century history is undeniable. From her humble, small-town upbringing to her rise to power as the United Kingdom's first female prime minister, to her dramatic fall from grace after more than three decades of service, celebrated biographer John Campbell delves into the story of this fascinating woman's life as no one has before. The result of more than nine years of meticulous research, The Iron Lady is the only balanced, unvarnished portrait of Margaret Thatcher, one of the most vital and controversial political figures of our time
Reprint. Originally published in Great Britain by Vintage in 2009.
Includes bibliographical references (p. 540-[554]) and index.
Keywords: Thatcher, Margaret; Conservative Party (Great Britain) -- Biography; Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 1979-1997.